Revisiting the normal stiffness–permeability relations for shale fractures under true triaxial stress - Fudong Li; Derek Elsworth; Xia-Ting Feng; Tianyu Chen; Jun Zhao; Yingchun Li; Jianyu Zhang; Qiong Wu; Guanglei Cui (Journal of Rock Mechanics and Geotechnical Engineering)
Understanding the relationship between normal stiffness and permeability in rock fractures under high and true-triaxial in situ stress conditions is critical to assess hydro-mechanical coupling in the Earth's crust. Previous data on stiffness–permeability relations are measured under uniaxial stress states as well as under normal stress. However, many projects involve faulted formations with complex three-dimensional (3D) stress states or significant changes to the original stress state. We rectified this by following the permeability evolution using a true-triaxial stress-permeability apparatus as well as independently applying a spectrum of triaxial stresses from low to high. The relationship between permeability and fracture normal stiffness was quantified using constraints based on the principle of virtual work. The impacts of fracture-lateral and fracture-normal stresses on permeability and normal stiffness evolution were measured. It was found that permeability decreases with increasing fracture-lateral and fracture-normal stresses as a result of Poisson confinement, independent of the orientation of the fracture relative to the stresses. The lateral stresses dominated the evolution of normal stiffness at lower normal stresses (σ3 = 10 MPa) and played a supplementary role at higher normal stresses (σ3 > 10 MPa). Moreover, correlations between the evolution of permeability and normal stiffness were extended beyond the low-stiffness, high-permeability region to the high-stiffness, low-permeability region under high fracture-lateral stresses (10–80 MPa) with fracture-normal stress (10–50 MPa) conditions. Again, high lateral stresses further confined the fracture and therefore reduced permeability and increased normal stiffness, which exceeded the previous reported stiffness under no lateral stress conditions. This process enabled us to identify a fundamental change in the flow regime from multi-channel to isolated channelized flow. These results provide important characterizations of fracture permeability in the deep crust, including recovery from deep shale-gas reservoirs.